2011
DOI: 10.1111/j.1443-1661.2011.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of hepatic hydatid cyst with biliary communication

Abstract: Endoscopic therapy is an effective mode of treatment for biliary fistulas complicating hepatic hydatid cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
9
0
3
Order By: Relevance
“…However, many other researchers have recommended using biliary prostheses in addition to ES for a couple of days to weeks [28, 29, 30]. Adas et al and Akçakaya et al demonstrated that using biliary stent or NBD in conjunction with ES improved treatment success when biliary strictures or choledocolithiasis accompanied high-output fistulas [28, 30].…”
Section: Discussionmentioning
confidence: 99%
“…However, many other researchers have recommended using biliary prostheses in addition to ES for a couple of days to weeks [28, 29, 30]. Adas et al and Akçakaya et al demonstrated that using biliary stent or NBD in conjunction with ES improved treatment success when biliary strictures or choledocolithiasis accompanied high-output fistulas [28, 30].…”
Section: Discussionmentioning
confidence: 99%
“…21 In another prospective study conducted by Sharma et al on patients with a hydatid cyst communicating with the bile duct, sphincterotomy with insertion of a nasobiliary drain (n = 6) or sphincterotomy with biliary stenting (n = 22) led to fistula healing in all patients after a median period of 11 (range, 5-45) days. 22 The removal of nasobiliary drainage catheters and stents was performed 8-45 days after stent placement. 22 Patients who were diagnosed with bile leak intraoperatively during cholecystectomy or those suspected with biliary injury should immediately undergo drain placement and ERCP.…”
Section: Staymentioning
confidence: 99%
“…22 The removal of nasobiliary drainage catheters and stents was performed 8-45 days after stent placement. 22 Patients who were diagnosed with bile leak intraoperatively during cholecystectomy or those suspected with biliary injury should immediately undergo drain placement and ERCP. However, our analysis did not show any significant difference in the outcome in relation to the timing of ERCP after the onset of bile leak between the two groups.…”
Section: Staymentioning
confidence: 99%
“…The liver is the most frequently affected organ in echinococcosis [ 1 ]. A common and severe complication in hepatic hydatid cyst disease is the communication between the cyst and the biliary tree [ 2 ]. However, fistulization between gallbladder and hydatid cyst is rare.…”
Section: Introductionmentioning
confidence: 99%